Desenvolvimento de banco de dados para condições de aderência em pavimentos aeroportuários - Gonçalves, Haikel Buganem Busgaib (2021)
Due to insufficient manipulability of airport infrastructure data currently stored by Agência Nacional de Aviação Civil (ANAC), and for its potential use in Airport Pavement Management Systems (APMS) activities, this research proposes a method of database construction for Brazilian airports pavement’s friction parameters. For this, tests were made with macrotexture and surface friction reports provided by ANAC, on Portable Document File (.pdf) format. Initially, two data collection methods were tested: (i) using Tesseract OCR (Optical Character Recognition), a software capable to read texts on images and turn them into editable files; and (ii) filling and manipulating formularies in Microsoft Excel (.xls) format. To verify the quality of data collected with Tesseract OCR, the Data Quality Index (DQI) was proposed. After testing the data colleting methods, flowcharts representing the data lifecycle and the database structure were developed. During this phase, an access key labeling method and a directory path system were proposed in order to users recover data intuitively. Lastly, a dynamic for database implementation and a hierarchy system were established for the main users: ANAC, the aerodrome operators and research entities. Although efficient to read simple texts, the OCR presented DQI varying between 0% and 98,75% while reading spreadsheets, not guaranteeing a suitable data quality. To test the capacity of the formulary methods, algorithms were made using Pandas library, capable of extracting data from formularies and printing them on text files (.txt) format; and constructing datasets on new .xls spreadsheets using the collected data. Thereby, data manipulated using the formulary method presented a suitable quality. The proposed data lifecycle created an organized database without duplicate access keys or directories. Therewith, it can be concluded that the database implementation allows: ANAC to obtain an auxiliary tool for regulation and monitoring activities; data to be access optimally by the research entities; and an appropriate network pavement management for the aerodromes operators.